Jejak Dan Pemikiran Keagamaan-Pendidikan La Malik Idris(1963-2009) - Muhammad Alifuddin (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
This study is the study deskripstif about: Traces and Religious Thought La Malik Idris. The focus of this study is the problem, how to trace and religious thought developed by La Malik Idris. As a descriptive study of the data of this study were collected through a series of in-depth interviews and the review of documents related to the study subject. Analysis of data obtained refers to the perspective of Miles and Huberman. The results of the study on a number of data obtained can be concluded that: La Malik Mujahid is the figure at the same propaganda propaganda academics. Keywords: Religious Thought, education, Da'wah